Failure to Diagnose Phaeochromocytoma Preoperatively: A Case Report and Review of Diagnostic Criteria - Ileana Antonopoulou; Mark Heining (Case Reports in Anesthesiology)
We present a case in which phaeochromocytoma was not diagnosed preoperatively despite extensive investigation. There was significant haemodynamic instability during surgery. We review current diagnostic criteria with a view to reducing such a risk in future.